ChemInform Abstract: A Selective C—H Insertion/Olefination Protocol for the Synthesis of α‐Methylene‐γ‐butyrolactone Natural Products. Issue 24 (27th May 2016) - Lloyd, Matthew G.; D'Acunto, Mariantonietta; Taylor, Richard J. K.; Unsworth, William P.
Abstract: An efficient one‐pot procedure is elaborated for the synthesis of a series of α‐methylene‐γ‐butyrolactones, including some natural products such as α‐cyclocostunolide (XIV).